Image of Bajau Kubang Sunduk on Omadal Island - Junior Kimwah; Zaimie Sahibil (Akademi Seni dan Teknologi Kreatif (ASTiF), Universiti Malaysia Sabah, 2022)
The pattern on the sunduk results from the high adaptation and observation by the sunduk maker of nature and its environment as well as the history of the person's life. The sunduk maker has such a high level of creativity that it is able to translate every element of nature around it into a form and pattern that is so unique and able to be conveyed visually to the community. The unique elements of life and beauty are translated through geometric and organic patterns engraved on each of the sunduk planes. The pattern on the exterior carving is used as a decoration and has an implicit meaning and can be understood through visual research. The effectiveness of the patterns is manifested when it is able to stand up for itself and tell a story without a voice. Patterns from the elements of the daily objects are also able to reinforce the story to be conveyed such as tasbih, keris, bujak and the crescent emblem as well as other decorative accessories. As a result, the sunduk maker cannot be different from the elements of manhood and femininity because the sunduk through life and her story as a man and woman will go through the twists and turns of her life as a woman. It is the twists of life that will adorn the sunduk through a pattern engraved on its plane.